Análise por sequenciamento paralelo maciço da resistência aos antirretrovirais em pacientes infectados pelo HIV-1 em terapia de resgate - Castro, Daniela Funayama de [UNIFESP] (2017)
Antiretroviral Therapy (ART) has improved the quality and life expectancy of HIV-1 infected individuals, reducing both mortality and morbidity. However, along with ART there was the emergence of resistant viral populations selected by the selective pressure of the drugs. These viral populations may lead the patient to virological failure. Although the success rates of ART are high, patients with virologic failure usually require changes in their antiretroviral regimens, which is called a "rescue therapy". Objectives: 1 - Analyze resistance mutations in samples of patients who failed ART and using rescue antiretrovirals: Darunavir, Etravirine and / or Raltegravir; 2 - Compare the mutational profile obtained by the Massive Parallel Sequencing with the one identified by conventional sequencing - Sanger's method. METHODS: Twenty-eight samples with HIV genotyping results with virological failure of antiretroviral drugs were selected between March 2014 and May 2015. The selected samples were from patients with failed ART and one or more antiretroviral drugs from this study. For the analysis of the samples the Massive Parallel Sequencing was done. Results: The most prevalent mutation among all analyzed was I84V in the protease (39.1%). Among the mutations that reduced susceptibility to Darunavir, after I84V, the most common was L33F, accounting for 26%. In mutations that confer reduced susceptibility to Etravirine, mutations K101P, Y181I and Y181V were identified, representing a frequency of 4.3% each. With regard to Raltegravir, a frequency above 21% of the N155H mutation was observed, which gives a significant reduction in the susceptibility to this drug. Mutations with minority prevalence and TAMs M41L, D67N, K70R, L210W, T215F, T215Y and K219Q were also identified. Conclusion: Minority resistance mutations are not currently identified by the method used in clinical practice, such as population sequencing (Sanger's method), whose detection limit is higher than 20-30%. Massive Parallel Sequencing makes it possible to identify mutations with frequency up to 1%. The analysis of minority mutations could, in some situations, help in the choice of a more adequate antiretroviral.The analysis of minority mutations could, in some situations, help in the choice of a more adequate antiretroviral.